1984
DOI: 10.1099/00221287-130-5-1169
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mudlac Transposons as Tools for Vital Staining to Visualize Clonal and Non-clonal Patterns of Organization in Bacterial Growth on Agar Surfaces

Abstract: When a histochemical stain for /I-galactosidase activity is applied to growth of Gram-negative bacteria on agar medium, the pigmentation is non-uniform and capable of revealing internal colony organization into different cell types. Use of an Escherichia coti strain with a thermosensitive lac repressor indicates that colonies expand by addition of new cells at the periphery and that older cells which have synthesized P-galactosidase early in development remain in the centre. Mixed inocula of different strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
3

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 14 publications
1
43
3
Order By: Relevance
“…However, the predominant mode of differentiation observed in these young colonies was concentric and thus independent of cell lineages. These observations on colony microstructure relate directly to earlier work on the control of largescale aspects of colony morphology (15)(16)(17)19), because it was the general rule that macroscopic boundaries, such as sector edges and concentric changes in colony structure, were marked by microscopic boundaries between bacterial groups that differed in cell size, cell shape, and cell alignments. The results thus provided an affirmative answer to the question of whether populations of nonswarming bacteria display identifiable changing patterns of multicellular organization as colonies develop.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…However, the predominant mode of differentiation observed in these young colonies was concentric and thus independent of cell lineages. These observations on colony microstructure relate directly to earlier work on the control of largescale aspects of colony morphology (15)(16)(17)19), because it was the general rule that macroscopic boundaries, such as sector edges and concentric changes in colony structure, were marked by microscopic boundaries between bacterial groups that differed in cell size, cell shape, and cell alignments. The results thus provided an affirmative answer to the question of whether populations of nonswarming bacteria display identifiable changing patterns of multicellular organization as colonies develop.…”
Section: Resultsmentioning
confidence: 68%
“…These methods were as described in previous publications (16)(17)(18)(19). As mentioned in the introduction, spot inoculations were used to initiate colony growth rather than stabbing, streaking, or spreading dilute suspensions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, such rings have been described previously when monitoring formation of araB-lacZ fusions carried by the bacteriophage Mu (46). Although these rings formed under quite different conditions and were continuous rings of ␤-galactosidase expression, rather than individual papilla, they are a result of Mu transposition, requiring transposase activity and Mu ends (48).…”
Section: Resultsmentioning
confidence: 86%
“…Although the microenvironment within bacterial colonies is poorly understood, several groups have recently shown that cell organization in them is highly ordered and that colony development is a morphogenetic process governed by genetic and environmental factors (3,5,(17)(18)(19). In Bacillus subtilis colonies, for example, cell separation or its absence following septation, as well as cell motility and chemotactic behavior or the lack thereof, are phenotypes that strongly influence colony form (10,13).…”
mentioning
confidence: 99%